Um novo modelo de disautonomia induzida pelo tratamento crônico com vincristina em ratos acordados - Peixoto Júnior, Arnaldo Aires (2008)
Vincristine is a chemotherapy drug and its use is limited by peripheral neuropathy with autonomic, sensory and motor involvement. Vincristine sulphate or saline was injected into the tail vein at doses of 50 µg/Kg (5 doses), 100 µg/Kg (2-5 doses) or 150 µg/Kg (1, 2 or 5 doses) QOD in 144 male Wistar rats (200-250g). Next day, they were gavage-fed with a test meal and sacrificed 10 minutes later. Gastric and intestinal dye recovery was determined by spectrophotometry. Basal mean arterial pressure (MAP) and heart rate (HR) and peak values of MAP and HR after i.v. phenylephrine 5 µg/Kg and atropine 0.5 mg/Kg were used to evaluate the baroreflex responses. Differences were evaluated by One-Way ANOVA with P<0.05. Chronic treatment with 5 doses of 50 µg/Kg; 3, 4 and 5 doses of 100 µg/Kg; 2 and 5 doses of 150 µg/Kg delayed gastric emptying (GE) (P<0.05). Two and 5 doses of 150 µg/Kg induced constipation and reduction in withdrawal latencies occurred after 1 dose of 50 µg/Kg, 100 µg/Kg and 150 µg/Kg (P<0.05). Vincristine (150 µg/Kg) immediately decreased fecal output (P<0.05). The effect of vincristine on the GE was not present in rats treated with 5 doses of vincristine 150 µg/kg one week and two weeks after the last dose (P>0.05). The withdrawal latency decrease lasted for at least 2 weeks after 5 doses of 150 µg/Kg (P<0.05). Vincristine enhanced the HR reduction induced by phenylephrine and enhanced cardiac response to atropine (P<0.05). Vincristine-induced autonomic neuropathy courses with delayed GE, altered baroreflex responses and increased colonic weight. Sensory neuropathy preceded and outlasted these autonomic changes.